But what if there's no chimney? - Thompson, Emily Weisner; Hussey, Mandy (Indiana University Press, 2016)
Five-year-old Ben is new in town and shocked to find his house has no chimney! How will Santa get into his house to deliver gifts' As Christmas approaches, Ben looks for answers, asking his dad, friend, teacher, mailman, and even his dog! Ben's search ends with a letter to Santa Claus, Indiana. Will Santa reply, and what will he say' Did you know that Santa Claus, Indiana is a real place' You can write to Santa and the Elves at P.O. Box 1, Santa Claus, Indiana 47579. Don't forget to include your return address to get a reply in December! Checkermint the elf is hiding inside! Can you find him'